COVID-19 in Pediatric Inpatients: A Multi-Center Observational Study of Factors Associated with Negative Short-Term Outcomes - Sara Rubenstein; Emily Grew; Katharine Clouser; Alexander Kwok; Aravindhan Veerapandiyan; Jeffrey Kornitzer; Keith Pecor; Xue Ming (Children, 2021)
Most cases of COVID-19 in children and adolescents are mild or asymptomatic, but a small number of individuals may develop severe disease, requiring PICU admission and/or mechanical ventilation. We assessed the factors associated with negative short-term outcomes of COVID-19 in 82 pediatric patients at three hospitals within the United States during the spring and summer of 2020 using medical records, laboratory data, and imaging studies of all patients admitted with a positive RT-PCR test for SARS-CoV-2. We found that older patients were more likely to have an extended hospital stay, and those with high BMIs (over 25) were more likely to be admitted to the PICU during the early pandemic. In addition, older patients, those with high BMIs, and those with underlying medical conditions, were more likely to receive respiratory support. Given the association of age, BMI, and underlying medical conditions with more severe COVID-19, clinicians should keep these factors in mind when treating patients.